Application of Referencing Techniques in EEG-Based Recordings of Contact Heat Evoked Potentials (CHEPS) - Anders, Malte; Anders, Björn; Kreuzer, Matthias; Zinn, Sebastian; Walter, Carmen (Frontiers in Human Neuroscience, 2020)
Evoked potentials in the amplitude-time spectrum of the electroencephalogram are commonly used to assess the extent of brain responses to stimulation with noxious contact heat. The magnitude of the N- and P- waves are used as a semi-objective measure of the response to the painful stimulus: the higher the magnitude, the more painful the stimulus has been perceived. The strength of the N-P-wave response is also largely dependent on the chosen reference electrode site. The goal of this study was to examine which reference technique excels both in practical and theoretical terms when analyzing noxious contact heat evoked potentials (CHEPS) in the amplitude-time spectrum. We recruited 21 subjects (10 male, 11 female, mean age of 55.79 years). We applied 7 noxious contact heat stimuli using two temperatures, 51 °C and 54 °C, to each subject. During EEG analysis, we aimed to identify the referencing technique which produces the highest N-wave and P-wave amplitudes with as little artifactual influence as possible. For this purpose, we applied the following 6 referencing techniques: mathematically linked A1/A2 (earlobes), average reference, REST, AFz, Pz and mathematically linked PO7/PO8. We evaluated how these techniques impact the N-P amplitudes of CHEPS based on our data from healthy subjects. Considering all factors, we found that mathematically linked earlobes to be the ideal referencing site to use when displaying and evaluating CHEPS in the amplitude-time spectrum.